Rhodium(I)-Catalyzed Intermolecular Hydroacylation of α-Keto Amides and Isatins with Non-Chelating Aldehydes - Kou, Kevin G. M. (Adv Synth Catal, 2015)
[Image: see text] The application of the bidentate, electron-rich bisphosphine ligand, 1,3-bis(dicyclohexyl)phosphine-propane (dcpp), in rhodium(I)-catalyzed intermolecular ketone hydroacylation is herein described. Isatins and α-keto amides are shown to undergo hydroacylation with a variety of non-chelating linear and branched aliphatic aldehydes. Also reported is the synthesis of new bidentate chiral phosphine ligands, and their application in hydroacylation is discussed.